Effects of Extracted Phenolic Compounds from Grape Seeds on Leptin, Adiponectin and Resistin Levels in Rats Fed with High Fat Foods - Entedhar Rifaat Sarhat; Husamuldeen Salim Mohammed Saeed; Siham A. Wadi (Tikrit Journal of Pure Science)
The current study was constructed to evaluate the efficacy of grape seed extracts (GSE) in management of obesity induced by high fat diet (HFD)-induced obesity in rats through assessment of the serum leptin,  adiponectin, and resistin. Experimental rats were divided into three groups: G:1 (healthy control), G:2 (obese control), G:3 (received100 mg/kg of GSE), after 7 weeks, serum leptin,  adiponectin, and resistin levels were measured in all groups.